Electronic effects of transition metal dopants on Fe(100) and Fe5C2(100) surfaces for CO activation. Issue 7 (4th March 2020) - Gong, Huiyong; He, Yurong; Yin, Junqing; Liu, Suyao; Qing, Ming; Peng, Qing; Huo, Chun-Fang; Wang, Hong; Yang, Yong; Wen, Xiao-Dong
Abstract : Spin polarized density functional theory computations were performed to elucidate electronic effects based on first-row transition metal doped Fe(100) and Fe5 C2 (100) surfaces for CO dissociation. Abstract : Spin polarized density functional theory computations were performed to elucidate electronic effects based on first-row transition metal doped Fe(100) and Fe5 C2 (100) surfaces for CO dissociation. Both Mn and Cr doped Fe(100) and Fe5 C2 (100) surfaces can enhance the dissociation of CO, while the Co, Ni and Cu doped ones are unfavorable for the dissociation of CO. Besides the BEP relationship, a linear relationship between activation energy and the electronegativity of the dopant atom is established. It can be deduced that the metals with lower electronegativity are favorable for the activation of CO. The reason has been analyzed by density of states and crystal orbital Hamilton population. The metals with lower electronegativity relative to Fe could donate electrons to doped sites and then activate CO with a more delocalized O 2p orbital. The electronic effects revealed herein are helpful for the understanding of the CO activation process and for the design of catalysts with desired activity.